2015
DOI: 10.1111/idh.12159
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study to measure anti‐erosion properties of a stabilized stannous fluoride dentifrice relative to a sodium fluoride/triclosan dentifrice

Abstract: Objective To compare the enamel protection efficacy of a stabilized stannous fluoride (SnF2) dentifrice to a sodium fluoride (NaF)/triclosan dentifrice following acidic erosive challenge. Methods In this in situ, randomized, controlled, double‐blind, two‐treatment, four‐period crossover clinical trial, subjects wore an appliance fitted with human enamel samples 6 h day−1 during each 15‐day treatment period. Twice each treatment day they swished with their assigned dentifrice slurry: 0.454% SnF2/0.077% NaF or 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 24 publications
6
24
0
Order By: Relevance
“…This study, using 10‐day treatment periods, demonstrated a significant erosion protection benefit of 93.5% for the multi‐benefit, 1100 ppm fluoride, high bioavailable stabilized stannous fluoride dentifrice compared to the triclosan‐containing dentifrice formulated with 1100 ppm fluoride as NaF. These results are consistent with other in situ clinical studies in the literature that have similarly demonstrated enhanced erosion protection, ranging from 27% to 94%, delivered from stabilized stannous fluoride dentifrices compared to other dentifrices that are not formulated with this ingredient . For example, a similar study by West et al found 68% greater erosion protection for a 0.454% stannous fluoride plus 0.077% sodium fluoride (1450 ppm fluoride) dentifrice marketed in the United Kingdom compared to a 1450 ppm fluoride NaF/triclosan dentifrice after 15 days of treatment and a 67% benefit after 10 treatment days.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This study, using 10‐day treatment periods, demonstrated a significant erosion protection benefit of 93.5% for the multi‐benefit, 1100 ppm fluoride, high bioavailable stabilized stannous fluoride dentifrice compared to the triclosan‐containing dentifrice formulated with 1100 ppm fluoride as NaF. These results are consistent with other in situ clinical studies in the literature that have similarly demonstrated enhanced erosion protection, ranging from 27% to 94%, delivered from stabilized stannous fluoride dentifrices compared to other dentifrices that are not formulated with this ingredient . For example, a similar study by West et al found 68% greater erosion protection for a 0.454% stannous fluoride plus 0.077% sodium fluoride (1450 ppm fluoride) dentifrice marketed in the United Kingdom compared to a 1450 ppm fluoride NaF/triclosan dentifrice after 15 days of treatment and a 67% benefit after 10 treatment days.…”
Section: Discussionsupporting
confidence: 87%
“…These results are consistent with other in situ clinical studies in the literature that have similarly demonstrated enhanced erosion protection, ranging from 27% to 94%, delivered from stabilized stannous fluoride dentifrices compared to other dentifrices that are not formulated with this ingredient. [19][20][21][22][23][24] For example, a similar study by West et al 19 found 68% greater erosion protection for a 0.454% stannous fluoride plus 0.077% sodium fluoride (1450 ppm fluoride) dentifrice marketed in the United Kingdom compared to a 1450 ppm fluoride NaF/triclosan dentifrice after 15 days of treatment and a 67% benefit after 10 treatment days. These study results are also consistent with recommendations from professional groups and organizations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Therefore, it is necessary to combine fluoride with other agents. 7 In this study, NaF had more anti-erosive effects only in relation to the negative control treated to distilled water, as previously reported 28 . Under acidic conditions, the NaF action of forming a CaF 2 layer on demineralized surfaces is reduced at low pH 9 .…”
Section: Discussionsupporting
confidence: 84%